EFFECTIVENESS OF EXECUTION FROM A BANK ACCOUNT - Mirosław Skawiński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper presents execution of a debtor’s bank account and the factors which, according to the author, influence directly its effectiveness. Despite the fact that the legislator seemingly has included a complete solution of this issue in the Code of Civil Proceedings, in the light of practical experience, the issue is more complicated and the solutions stated in the regulations cause serious trouble to the creditors, debtors, executive authorities as well as banks. The paper describes different types of bank accounts, for which it is possible to proceed with the execution, methods of searching for bank accounts by the executive authorities, and also the impact of Article 54 of banking law, which involves restriction on the execution.